The (Im)Possibility of Academic Integrity in John Williams’s Stoner - Matek, Ljubica; Rehlicki, Jasna Poljak (FOCUS: Papers in English Literary and Cultural Studies, 2018)
Written in 1965, Stoner, the recently re-discovered academic novel by John Williams (1922-1994) deals with a variety of intriguing issues such as the role of literature in the personal growth of an individual, the tension between private desires and social customs, and the role of family in an individual’s life.1 By some, it was read as “an all-American success story …[about] socio-economic mobility through hard work, individual effort, and merit” (Wald 2). Our paper, however, will focus on the portrayal of issues such as academic integrity and the perception of academics and academic work. Williams’s novel, not only through the story it tells, but also as an object, as a work of art, seems to reflect on the worrying idea of the irrelevance of the humanities, the humanist way of thinking, and humanist preoccupations, and does this in a way that is rather untypical of most campus novels.